Silver Creek Bodyguard - McKenna, Lindsay, 1946- (New York : Zebra Books Kessington Publishing Corp., 2022)
"New York Times bestselling author, US Navy Veteran, and genre pioneer Lindsay McKenna combines pulse-pounding suspense with the romance of a contemporary Western for the fourth installment in her highly emotional, engrossingly swoon-worthy, Wyoming-set Silver Creek series. Can a veteran SEAL protect a woman from her past when it comes unexpectedly calling?" --
Keywords: Man-woman relationships -- Fiction; Women -- Fiction; Herbs -- Therapeutic use; Fiction; Bodyguards -- Fiction; Veterans -- Fiction; Wyoming -- Fiction; Thrillers (Fiction); Romance fiction